Padbagay - Andhika Rahmadhanur; Desfiarni Desfiarni (SENDRATASIK UNP, 2021)
This dance work aims to create a dance work which trains and educates a choreographer to become a creative choreographer in preparing ideas through innovative moves as the language in a dance work. The theme in this dance work is about adaptation. The work of this dance is a dramatic dance with a representational symbolic performance. The dance work "PADBAGAY" is taken from Philippine Tagalog which means adaptation, and the dance work is inspired by the life of parents of a dance stylist whose mother is Filipino and the father is from Minangkabau. This work tells about the struggle of the Filipino woman in adapting to Minangkabau culture from her husband's family.